A detached petal disc assay and virus-induced gene silencing facilitate the study of Botrytis cinerea resistance in rose flowers. Issue 1 (1st December 2019) - Cao, Xiaoqian; Yan, Huijun; Liu, Xintong; Li, Dandan; Sui, Mengjie; Wu, Jie; Yu, Hongqiang; Zhang, Zhao
Abstract: Fresh-cut roses ( Rosa hybrida ) are one of the most important ornamental crops worldwide, with annual trade in the billions of dollars. Gray mold disease caused by the pathogen Botrytis cinerea is the most serious fungal threat to cut roses, causing extensive postharvest losses. In this study, we optimized a detached petal disc assay (DPDA) for artificial B. cinerea inoculation and quantification of disease symptoms in rose petals. Furthermore, as the identification of rose genes involved in B. cinerea resistance could provide useful genetic and genomic resources, we devised a virus-induced gene silencing (VIGS) procedure for the functional analysis of B. cinerea resistance genes in rose petals. We used RhPR10.1 as a reporter of silencing efficiency and found that the rose cultivar 'Samantha' showed the greatest decrease in RhPR10.1 expression among the cultivars tested. To determine whether jasmonic acid and ethylene are required for B. cinerea resistance in rose petals, we used VIGS to silence the expression of RhLOX5 and RhEIN3 (encoding a jasmonic acid biosynthesis pathway protein and an ethylene regulatory protein, respectively) and found that petal susceptibility to B. cinerea was affected. Finally, a VIGS screen of B. cinerea -induced rose transcription factors demonstrated the potential benefits of this method for the high-throughput identification of gene function in B. cinerea resistance. Collectively, our data show that the combination of the DPDA and VIGS is a reliable and high-throughput method for studying B. cinerea resistance in rose.